Mellanhandens roll i certifieringskedjan : en fallstudie på Svenskt Sigill - Breitholtz, August; Hempel, Lukas (SLU/Dept. of Economics, 2020)
In a globalised world where food is exported and imported around the earth there are high demands on the quality and safety of the food. One way to meet these demands are through certifications, which simply means the food follows a certain set of standards. Certifications come in several different formats, but the most well-known kind are logos on packaging that range from fair trade to organic. Behind every certification are several actors that play an active role to bring the certification forth. One of these actors is the advisor which is an actor that is seldom talked about in the context of certification. The purpose of this study is to generate a conceptual understanding of the role of intermediaries in the chain of certification through a case study of Svenskt Sigill. The study makes use of a qualitative research method in which semi-structured interviews were conducted with key actors in the certification process. The interviews are focused on the relation between the actors and their relation to the certification in question. For this purpose, a combination of literature regarding certification and theories about intermediaries been utilized to assess the different actors’ roles in the process certification for Svenskt Sigill. This has been accomplished by building a "chain of certification" that describes the process of implementing the certifications owned by Svenskt Sigill. Intermediary theory is then applied to the "chain of certification" to determine the capacity of the actors. The results of the study show that the intermediaries in this case are the auditor and the advisor. The auditor lends its credibility to the producer and their product. This serves to guarantee that the product follows a certain expected quality to the producer’s customer and customer's customers. The role of the advisor has been interpreted in this study as more important than previously assumed. The advice and knowledge this actor contribute to the producer and Svenskt Sigill is considered significant and thus the advisor is hard to part with.